2002
DOI: 10.1097/00000372-200212000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Balanitis of Zoon

Abstract: Balanitis of Zoon is a relatively common diagnosis in elderly men, although its nature is controversial and descriptions of its histopathologic features in current textbooks of dermatopathology vary considerably. We studied 45 cases of balanitis of Zoon clinically and histopathologically. The earliest histopathologic changes in cases diagnosed clinically as balanitis of Zoon were slight thickening of the epidermis, parakeratosis, and a patchy lichenoid infiltrate of lymphocytes and some plasma cells. More adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 24 publications
1
40
1
Order By: Relevance
“…Its exact cause remains unknown. PCBZ may occur either as an isolated finding or may coexist with or complicate other entities [12,13,14,15,16] that may be seen in the same patient at different time points or arise in the chronically inflamed mucosae of PCBZ [17]. Unlike some other inflammatory penile dermatoses, PCBZ is regarded as a benign condition and not considered to be a precursor for neoplasia [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its exact cause remains unknown. PCBZ may occur either as an isolated finding or may coexist with or complicate other entities [12,13,14,15,16] that may be seen in the same patient at different time points or arise in the chronically inflamed mucosae of PCBZ [17]. Unlike some other inflammatory penile dermatoses, PCBZ is regarded as a benign condition and not considered to be a precursor for neoplasia [14].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy of the lesion is usually necessary to confirm the diagnosis and rule out other conditions that are considered in the differential diagnosis, such as fixed drug eruptions, seborrheic eczema, lichen planus, lichen sclerosus et atrophicus, cicatricial pemphigoid, penile intraepithelial neoplasia (erythroplasia of Queyrat), squamous cell carcinoma, Kaposi's sarcoma, contact dermatitis or psoriasis [7,16,20,21,22]. Histologically, epidermal edema, a dense upper dermal band of chronic inflammatory cells, including many plasma cells, dilated capillaries, extravasated red blood cells, and hemosiderin deposition, is observed [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent histopathological study performed on this topic is the one published by Weyers et al in 2002 [6]. Reviewing a series of cases, these authors found a sequence in the evolution of lesions from a patchy lichenoid pattern to a dense plasmacytic infiltrate with possible prominent fibrosis in the latest stages.…”
Section: Discussionmentioning
confidence: 99%